THE HATCHING OF JAVA COMBTAIL (Belontia hasselti) EGGS IN MEDIA WITH DIFFERENT pH LEVELS - Danang Yonarta; Ayu Maslamia; Mochamad Syaifudin; Madyasta Anggana Rarassari (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2026)
The production of java combtail fry still relies heavily on wild catches, necessitating the development of semi-natural breeding techniques. One important factor influencing hatching success is the medium's pH. The pH value influences the activity of the enzyme chorionase, which softens the chorion, making the eggshell softer and facilitating hatching. This study aims to determine the optimal pH for the Java combtail hatching medium. The research method employed a completely randomized design (CRD) with 5 treatments and 3 replicates. The pH treatments for hatching were: medium pH 4±0.3 (P1), pH 5±0.3 (P2), pH 6±0.3 (P3), pH 7±0.3 (P4), and pH 8±0.3 (P5). The results showed that different pH levels in the hatching medium significantly affected hatching percentage, hatching duration, fry survival, fry length growth, and absolute fry weight. However, they had no significant effect on the percentage of larval abnormalities. P4 was the best treatment, yielding the highest hatching percentage of 90.00±0.82%, a hatching duration of 27.33±0.14 hours, and a larval survival rate of 96.19±2.43%, no larval abnormalities, absolute length growth of 4.94±0.05 mm, and absolute weight growth of 0.042±0.0010 g. This is likely because a pH of 7 (P4) represents the optimal condition supporting chorionase enzyme activity, thereby accelerating chorion softening and enhancing hatching success. Water quality during the study remained within the tolerance range for hatching and rearing of mudskipper fry. The research results serve as a reference for mudskipper fish farmers.